2015
DOI: 10.1021/acs.langmuir.5b02560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supporting Polyelectrolyte Multilayers and Deposition Conditions on the Formation of 1-Palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine/1-Palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine Lipid Bilayers

Abstract: The formation of complete supported lipid bilayers by vesicle adsorption and rupture was studied in relation to deposition conditions of vesicles and underlying cushion formed from various polyelectrolytes. Lipid vesicles were formed from zwitterionic 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and negatively charged 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE) in phosphate buffer of various pH with or without NaCl addition. Polyelectrolyte multilayer films (PEM) were constructed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…This may indicate a mixed population of vesicles and lipid bilayer . Previous studies by Wlodek et al monitoring vesicle rupture on polyelectrolyte coated surfaces, have shown Δf and ΔD values of up to −82 Hz and 28 × 10 −6 , respectively, concluding that the high shifts are caused by abundant water trapped in hydrophilic regions . Further confirmation of the effect of thickness on vesicle adsorption and fusion is shown in Figure S3 of the Supporting Information.…”
Section: Resultssupporting
confidence: 55%
“…This may indicate a mixed population of vesicles and lipid bilayer . Previous studies by Wlodek et al monitoring vesicle rupture on polyelectrolyte coated surfaces, have shown Δf and ΔD values of up to −82 Hz and 28 × 10 −6 , respectively, concluding that the high shifts are caused by abundant water trapped in hydrophilic regions . Further confirmation of the effect of thickness on vesicle adsorption and fusion is shown in Figure S3 of the Supporting Information.…”
Section: Resultssupporting
confidence: 55%
“…Thus, these results show that the amount of liposomes adsorbed, the kinetics of liposome fusion and rupture, as well as the final structure and amount of the obtained SLBs depended on the PEM cushion type, demonstrating the important role of the PEM properties in the SLB formation via vesicle fusion. 20 Our findings are in agreement with a number of previous studies. Renner et al 29 found that the degree of hydrophobicity and swelling of the anionic polymer cushions determined both the kinetics of the membrane formation and the mobility of the obtained SLB.…”
Section: Introductionsupporting
confidence: 94%
“…Considering the results for supported lipid bilayer formation on the top of PEI(PGA/PLL) 3 , PEI(PSS/PDADMAC) 3 and PEI(PSS/PEI) 3 discussed previously 20 and in the Introduction section, we can correlate the capacity of the SLB formation with the polar component of the surface free energy of polyelectrolyte cushion. While the kinetics of liposome deposition is the same for all the studied PEM supports (Fig.…”
Section: Positively Terminated Multilayers Negatively Terminated Multmentioning
confidence: 97%
See 1 more Smart Citation
“…27,28 This is likely due to an inhibition of rupture propagation. The surface roughness of PLGA microspheres prepared by solvent evaporation has been previously measured to be approximately 12 nm or below 29 which reaches the limit suggested Duarte and Raposo.…”
Section: Resultsmentioning
confidence: 99%